Effect of Oxyethilated Glycerol Cryoprotectants on DPPC Model Lipid Membranes Structure and Phase - Krasnikova, Alina O.; Kasian, Natalia A.; Vashchenko, Olga V.; Lisetski, Longin N.; Kompaniets, Antonina M.; Zinchenko, Aleksandra V.; Soloviov, Dmitriy V.; Bulavin, Leonid A. (Problems of Cryobiology and Cryomedicine, 2015)
N/A